Intra-operative use of one-step nucleic acid amplification (OSNA) for detection of the tumor load of sentinel lymph nodes in breast cancer patients - Heilmann, Thorsten; Mathiak, Micaela; Hofmann, Jakob; Mundhenke, Christoph; Van Mackelenbergh, Marion; Alkatout, Ibrahim; Wenners, Antonia; Eckmann-Scholz, Christel; Schem, Christian (Journal of Cancer Research and Clinical Oncology, 2013)
Background: The purpose of this single-center study was to determine the practicability of the intra-operative use of one-step nucleic acid amplification (OSNA) as the only method for detection of SLN. The OSNA system has been well described and is supposed to be as accurate as conventional histology. Methods: Three hundred and thirty SLNs from 143 breast cancer patients were analyzed in an intra-operative setting. The CK19-copy number was determined by OSNA and divided into 3 results ("-" no metastasis; "+" micrometastasis; "++" marcometastasis). If OSNA gave a positive result, an axillary lymph node dissection was carried out during the same session. The central 1-mm slice of each node was obtained for permanent histology. Additionally, the results were correlated to clinicopathological factors, and the time for the intra-operative use was evaluated. Results: Thirty-nine of the 143 patients were OSNA positive, 22 with macrometastatic and 17 with micrometastatic spread. The mean time for the OSNA run with one SLN was 34.4 min. We could show a correlation between the tumor size and OSNA positivity as well as between the numbers of OSNA positive SLNs with the tumor load of associated non-SLNs. Furthermore, we found that a cutoff CK19 copy number of 7,900/μL indicates a positive non-SLN result with the highest sensitivity (91 %) and specificity (61 %). Conclusion: We found OSNA to be very helpful for the intra-operative determination of the tumor load of a SLN as a basis for decision-making concerning further surgical axillary intervention. OSNA allows precise differentiation of micro- from macrometastasis, and the CK19 copy number predicts the probability of tumor load in other axillary lymph nodes and might help to find adequate adjuvant treatment options. This objective method is well suitable for everyday use and may reduce the pathologic workload and the risk of secondary operative interventions with all associated costs and stress for the patients. © 2013 European Union.
CRIS-Team Scopus Importer:2022-11-17
Keywords: Breast cancer; Carcinoma; CK19; Nucleic acid amplification/OSNA; Sentinel lymph node/SLN; Tumor load